Interferon-beta inhibits human glioma stem cell growth by modulating immune response and cell cycle related signaling pathways - Han, Xin-Xin; Jin, Shengkai; Yu, Li-Ming; Wang, Min; Hu, Xin-Yu; Hu, Dai-Yu; Ren, Jie; Zhang, Meng-Han; Huang, Wei; Deng, Jia-Jia; Chen, Qing-Qing; Gao, Zhengliang; et al. (Cell regeneration, 2022)
Malignant Glioma is characterized by strong self-renewal potential and immature differentiation potential. The main reason is that malignant glioma holds key cluster cells, glioma stem cells (GSCs). GSCs contribute to tumorigenesis, tumor progression, recurrence, and treatment resistance. Interferon-beta (IFN-β) is well known for its anti-proliferative efficacy in diverse cancers. IFN-β also displayed potent antitumor effects in malignant glioma. IFN-β affect both GSCs and Neural stem cells (NSCs) in the treatment of gliomas. However, the functional comparison, similar or different effects of IFN-β on GSCs and NSCs are rarely reported. Here, we studied the similarities and differences of the responses to IFN-β between human GSCs and normal NSCs. We found that IFN-β preferentially inhibited GSCs over NSCs. The cell body and nucleus size of GSCs increased after IFN-β treatment, and the genomic analysis revealed the enrichment of the upregulated immune response, cell adhesion genes and down regulated cell cycle, ribosome pathways. Several typical cyclin genes, including cyclin A2 ( CCNA2) , cyclin B1 ( CCNB1) , cyclin B2 ( CCNB2), and cyclin D1 ( CCND1) , were significantly downregulated in GSCs after IFN-β stimulation. We also found that continuous IFN-β stimulation after passage further enhanced the inhibitory effect. Our study revealed how genetic diversity resulted in differential effects in response to IFN-β treatment. These results may contribute to improve the applications of IFN-β in anti-cancer immunotherapy. In addition, these results may also help to design more effective pharmacological strategies to target cancer stem cells while protecting normal neural stem cells.